MORAL VALUES OF THE MAIN CHARACTER IN MALAY FOLKLORE "THE HISTORY OF BATU BARA" - Mafazah, Lailatul (RETAIN, 2021)
As a form of expression or stories lived and developed by traditional people, folklore has an important role in the education field. The moral values of the main character obtained in folklore can be a good lesson and good model character for the reader. This study aimed to identify and describe the moral values of the main character delivered in the Malay folklore entitled "The History of Batu Bara". This method of research is the descriptive qualitative method. The source of data used of the research is a story taken from book entitled “Antologi Cerita Rakyat Batu Bara” written by Yolveri et al., and published by Balai Bahasa Provinsi Sumatera Utara Badan Pengembangan dan Pembinaan Bahasa Kementerian Pendidikan dan Kebudayaan. The findings of this research found that the twelve moral values of the main character can be used as a good moral lesson. These moral values ​​namely: (1) respect for humans, (2) Respect for women, (3) dedicated, (4) fair, (5) loyal, (6) friendly, (7) polite, (8) trustworthy, (9) democratic, (10) respect for sexuality and family life, (11) nationalist, (12) respect for culture and tradition.